2022
DOI: 10.1038/s41598-022-25201-6
|View full text |Cite
|
Sign up to set email alerts
|

The proliferation of atypical hepatocytes and CDT1 expression in noncancerous tissue are associated with the postoperative recurrence of hepatocellular carcinoma

Abstract: Recently, we reported that extent of proliferation of atypical hepatocytes (atypical hepatocytes) was most important histological risk factor for development of hepatocellular carcinoma (HCC) from chronic hepatitis C or liver cirrhosis. Here, we aimed to clarify whether the atypical hepatocytes in noncancerous sections is also involved in postoperative recurrence. Furthermore, we investigated significant genes involved in the atypical hepatocytes. Association between the extent of atypical hepatocytes in nonca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
32
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(44 citation statements)
references
References 51 publications
2
32
0
Order By: Relevance
“…Many studies have revealed relevant risk parameters for its progression in malignant hepatocellular neoplasms ( Moriyama et al, 2022 ; Park et al, 2022 ; Yang et al, 2022 ). However, the increased incidence of hepatocellular carcinoma in Wilson’s patients and in animal models has raised researchers’ concerns that abnormal copper accumulation may be related to an unidentified mechanism of tumor progression ( Ge et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have revealed relevant risk parameters for its progression in malignant hepatocellular neoplasms ( Moriyama et al, 2022 ; Park et al, 2022 ; Yang et al, 2022 ). However, the increased incidence of hepatocellular carcinoma in Wilson’s patients and in animal models has raised researchers’ concerns that abnormal copper accumulation may be related to an unidentified mechanism of tumor progression ( Ge et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Definitive diagnosis of HCC was made by histological diagnosis or by abdominal angiography, which was performed when HCC nodule was suspected by contrast-enhanced abdominal ultrasonography (CEUS) or computed tomography (CT). ( 2 , 5 ) Cases visited the outpatient clinic every 1 to 3 months and underwent CT or AUS every 6 months after IFN treatment, depending on the degree of F stage.…”
Section: Methodsmentioning
confidence: 99%
“…For histologic evaluation, the score of each parameter and the histologic findings related to the development of HCC were examined according to previous reports. ( 2 6 ) Liver biopsy tissues were obtained from CHC and LC by percutaneous needle biopsy (Tru-Cut Soft Tissue Biopsy Needle, 14 G; Baxter, Deerfield, IL; or BARD MONOPTY Tru Guid, 14 G; Medicon, Tokyo, Japan). Liver tissues obtained by needle biopsy were fixed in 10 to 20% buffered formalin and embedded in paraffin.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations